Problems of training program variable component. - Shyyan O.I; Kravchenko N.S (Kharkov National Pedagogical University, 2012)
The problems of introduction of on-line tutorial are considered to on physical culture which is based on principle of variability. The results of questioning of teachers of physical culture are resulted. 100 teachers answered on a question of questionnaire, in age from 25 to 65 years. It is set that swingeing majority of specialists adhere to methodical recommendations in relation to introduction of on-line tutorial and its variability constituent. It is discovered that at application of variability educational program units teachers have certain difficulties: unsatisfactory state of material and technical base and level organizationally to the methodical help; absence of the proper terms for the high-quality leadthrough of lessons. The necessity of increase of efficiency of different forms of the methodical providing is marked - district, city methodical associations of teachers, seminars and master classes. It is set that the lack of application of variability educational program units is absence in maintenance of on-line tutorial of pointing in relation to teaching of educational material for children with a hyposthenic health (preparatory and special medical groups)